Coercivity enhancement by inhibiting the formation of coarse grains region in hot-deformed Nd-Fe-B magnets with WC nano-particles addition. (15th April 2017) - Zheng, Xiaofen; Li, Ming; Chen, Renjie; Lei, Fang; Jin, Chaoxiang; Wang, Zexuan; Ju, Jinyun; Yin, Wenzong; Lee, Don; Yan, Aru
Abstract: Anisotropic ultrafine-grained Nd-Fe-B magnets with WC addition were prepared by hot deformation. With WC nano-particles addition of ~ 1.0 wt.%, the squareness was optimized and the coercivity of the hot-deformed magnets increased substantially by 2.16 kOe, from 15.59 to 17.75 kOe without expense of the remanent magnetization. The observation for microstructure revealed that the WC nano-particles mainly existed on the interfaces of melt-spun ribbons. Meanwhile, due to the local compressive stress induced by the hard WC nano-particles, the deformability of neighboring grains was remarkably enhanced which leads to the reduction of the coarse grain regions. Graphical abstract: